2000
DOI: 10.1073/pnas.190256997
|View full text |Cite
|
Sign up to set email alerts
|

Portosystemic shunting and persistent fetal vascular structures in aryl hydrocarbon receptor-deficient mice

Abstract: A physiological examination of mice harboring a null allele at the aryl hydrocarbon (Ah) locus revealed that the encoded aryl hydrocarbon receptor plays a role in the resolution of fetal vascular structures during development. Although the aryl hydrocarbon receptor is more commonly studied for its role in regulating xenobiotic metabolism and dioxin toxicity, a developmental role of this protein is supported by the observation that Ah null mice display smaller livers, reduced fecundity, and decreased body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
272
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(283 citation statements)
references
References 46 publications
11
272
0
Order By: Relevance
“…In the mammalian fetus and in fish larvae, the AHR plays prominent roles in both resolving vascular structures and mediating cardiovascular toxicities of TCDD (Lahvis et al, 2000;Bello et al, 2004). In mammals, the importance of functional AHR is demonstrated in AHR-null mice by a failure of a fetal vascular structure, the ductus venosus, to close, thus permitting blood from the portal vein to bypass the liver by shunting to the inferior vena cava.…”
Section: Effects Of Tcdd Exposure On Development Ahr In Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In the mammalian fetus and in fish larvae, the AHR plays prominent roles in both resolving vascular structures and mediating cardiovascular toxicities of TCDD (Lahvis et al, 2000;Bello et al, 2004). In mammals, the importance of functional AHR is demonstrated in AHR-null mice by a failure of a fetal vascular structure, the ductus venosus, to close, thus permitting blood from the portal vein to bypass the liver by shunting to the inferior vena cava.…”
Section: Effects Of Tcdd Exposure On Development Ahr In Developmentmentioning
confidence: 99%
“…In mammals, the importance of functional AHR is demonstrated in AHR-null mice by a failure of a fetal vascular structure, the ductus venosus, to close, thus permitting blood from the portal vein to bypass the liver by shunting to the inferior vena cava. Functional AHR is also required for normal vascular "pruning" during fetal development, the absence of which results in the propagation into maturity the highly anastomotic vasculature architecture of the liver, eye and kidney that that are characteristically neonatal (Lahvis et al, 2000).…”
Section: Effects Of Tcdd Exposure On Development Ahr In Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The wide range of toxic effects induced by these compounds, including birth defects, impaired reproductive capacity and altered immune responses, have encouraged research on the interaction of AhR with sex steroid receptors and the immune system (Ohtake et al, 2008;Quintana et al, 2008;Veldhoen et al, 2008). AhR regulates cellular differentiation during development (Huang et al, 2004;Lahvis et al, 2000) and may promote cell cycle progression in the absence of exogenous ligand (Chang et al, 2007;Marlowe and Puga, 2005). There is also an emerging evidence for a prominent role of AhR in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…AhR is also known to affect vascular development, as demonstrated by persistent ductus venosus and microvasculature abnormalities in the livers of AhRnull mice. 14 Recently, it has been demonstrated that 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) exposure severely impairs the regenerative ability of partially excised mouse livers, 15 an effect most likely mediated through AhR. On the other hand, TCDD is also known to be a potent tumor promoter in mouse liver.…”
mentioning
confidence: 99%